CHINESE IMMIGRANT’S SEARCHING FOR CULTURAL IDENTITY IN LIAN GOUW’S ONLY A GIRL - Wahyono, Danu (TANDA, 2024)
This study explores “Chinese Immigrant's Searching for Cultural Identity in Lian Gouw’s Only a Girl”. It aims to discuss how a Chinese girl searches for cultural identity, meanwhile the objectives of the study are the effort to search cultural identity, the problems, and the impacts of searching cultural identity. It uses a qualitative method as the research design and sociological approach as a literary approach. The result shows that Jenny coming from a Chinese immigrant family searches her cultural identity due to her different cultural identity she has. She raised in a Dutch culture is given a western name and introduced to western culture. The change of political situation after the post-independence period makes her difficult in searching cultural identity. She gets difficulties in navigating cultural identity. As she is unaccustomed to use the Indonesian culture, she encounters many challenges that generate a cultural conflict to adapt a new cultural identity. As a result, she changes her worldview and life decision. The findings of this study indicate that the efforts of searching and adapting cultural identity come from her family, such as giving a western name, and introducing a western culture. But the change of political situation, she gets difficulties in assimilating the Dutch culture. She changes her worldview and life decision by going to America to study a Veterinarian. Therefore, the cultural identity is socially constructed through conflicts.